Analyzing Core Drivers of Societal Changes in Ready to Wear Garment Industry of India (Vallis Aurea, 2019)
Markets is a social system supplying society’s material needs. In today’s scenario in India, because of fast socio-cultural changes, audiences have high exposures, information and knowledge about trends, availabilities, options and uniqueness of products available and entering the market. Hence businesses need a very careful and cautious handling of the aforesaid fact in strategic planning. Manifestation of dominating societal aspects viz. social media, societal & cultural changes, rise of newer market segments, vulnerable yet aspirational youth and growing consciousness in producers & marketers are propelling the wheel of change in marketing strategies, in Indian garment market in the light of aspects like change in mindset & attitude, changing life styles, quick changing buying & usage behaviors, changing social exposures etc.In this context, companies require to analyzechange drivers of the sector to consider changing societal elements and their impact on the target segments in order to frame sustainable marketing strategies. The significance of such “change drivers” has increased in recent years in India, especially after entry and success of “affordable Chinese product” in all the segments , making it essential to understand issues like changing mindsets and societal status of customers. Now such changes require in-depth study, analysis and inclusion in strategic planning to cater and engage the target better. This need of incorporation of changes drivers in strategic planning is studied in context to ready to wear garments sector of India as this sector it is not only about selling the product but it is all about selling a life style under changing customer perception. This study will help in understanding and incorporating changing societal influences to include them in strategic planning, product development and marketing with holistic approach.